الاتجاهات العامة للنفقات التحويلية لبلدان عربية مختارة للمدة 1980-2002 - د. هاشم محمد العركوب; عدي سالم علي الطائي (PROSPECTIVE RESEARCHES, 2023)
This study explains widely the transfer expenses, through shedding light on its internal and external form and the relationship of transfer expenses with the structural adaptation of the government expenses polices, the basic purpose of the state in providing this kind of expenses. The study shows the amount of transfer expenses, and each term its contents in nine Arabic countries, Jordan, Oman, Yemen, Bahrain, Kuwait, Egypt, Tunisia, Morocco, Iraq, for the period (1980-2002). The period is divided into five sub-periods in order to capture the most important development occurred during the mentioned periods. However, the study explains and interprets the trends of transfer expenses, and follows up the accompanied changes in each term of its terms. It also tries to interpret the reasons behind those changes, which show direct influence upon the trend of transfer expenses such as allotting programs demographic, factors wars, and economic crises. The hypothesis of the study proves that the state supportive programs increase gradually with time. While they decrease when allotting programs are applied. The study also proves that interest payments play an active role in increasing the transfer expenditure in non-oil countries.